Detection of Weligama Coconut Leaf Wilt Disease Phytoplasma by Real-Time Polymerase Chain Reaction - Wijesekara, H.T.R.; Perera, S.A.C.N.; Bandupriya, D.; Meegahakumbura, M.K.; Perera, Lalith (International Coconut Community Journal, 2020)
Weligama Coconut Leaf Wilt Disease (WCLWD) is a non-lethal, but debilitating phytoplasma disease found in coconut palms in Sri Lanka which is confined to the Southern Province of the country, well-away from the major coconut growing area. If it spreads to the major coconut growing area, it might severely damage the coconut industry in Sri Lanka. Government commenced a disease control program to eradicate the disease and, more importantly to prevent spreading of the disease to major coconut growing areas. The major constraint in this program is the lack of an accurate and reliable method for identifying affected palms. Visual symptoms are used to identify the affected palms for removal, yet growers are not always convinced of the method of resisting palm removal. This poses a serious threat to the implementation of the disease control program. Although a Nested-PCR-based disease diagnosis was established earlier, the detection rate and reliability need further improvements. Therefore, an urgent necessity for a more reliable disease detection method has arisen. In the current study, a Real-Time Polymerase Chain Reaction (qPCR) powered by a pair of primers and a probe designed from the published partial sequences of the WCLWD phytoplasma was validated with 202 coconut samples and a detection rate of above 95% was achieved. This newly established detection system was highly reliable and a way forward for controlling the WCLWD disease in Sri Lanka.